Tantangan dan Peluang Kurikulum CHALLENGES AND OPPORTUNITIES OF THE ISLAMIC RELIGIOUS EDUCATION (PAI) CURRICULUM AT ARMANIYAH VOCATIONAL HIGH SCHOOL (SMK) BEKASI IN FACING MODERN WORK DEMANDS - Edy, Sarwo; Sumarta, Sumarta (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: In the context of vocational education increasingly influenced by the demands of the modern workforce, the Islamic Religious Education (PAI) curriculum at SMK Armaniyah Bekasi faces challenges in aligning religious values with the practical skills required in the workplace. Purpose: This study aims to identify the challenges and opportunities faced by the PAI curriculum in preparing students for the demands of the modern workforce. Method: Using a descriptive qualitative approach and case study method, the research analyzes the gap between the existing curriculum content and the skills needed in the labor market. Data was collected through interviews, observations, and document analysis. Result: The findings indicate that the PAI curriculum at SMK Armaniyah focuses more on religious theory, neglecting the development of practical skills required by the workforce. Conventional teaching methods also pose a barrier to the development of students' competencies. Conclusion: However, the study identifies several opportunities, such as the integration of work ethics, the use of technology in teaching, and collaboration with the industry. To enhance the relevance of the PAI curriculum, it is recommended that the school develop a curriculum focused on skills and social values, while also leveraging technology and industry partnerships to provide students with direct work experience.